MASA DEPAN HAK CIPTA: TINJAUAN KEABSAHAN HASIL KARYA KECERDASAN ARTIFISIAL DI INDONESIA - Rizki Fauzi; Tasya Safiranita Ramli; Rika Ratna Permata (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The increasingly dynamic development of technology has always had an impact in various sectors including on the copyright intellectual property regime that continues to experience digital disruption. One such disruption comes from the presence of artificial intelligence that is currently able to make works autonomously without human intervention. This actually led to a paradigm shift related to the work that was originally attached in the direct relationship between the Creator and his work as philosophical intellectual property protection began to change due to artificial intelligence. Therefore, there are legal issues related to the validity of artificial intelligence works and the future of copyright law in Indonesia because currently the existing regulations have not clearly accommodated artificial intelligence. Research methods using normative juridical approaches with descriptive analysis methods and literature studies of primary, secondary, and tertier legal materials, then conducted legal comparisons with the European Union. The results of the study will show the status of artificial intelligence works based on the Copyright Law and legal reconstruction as the results analysis of ius constituendum of copyright in Indonesia